STRATEGI PEMENANGAN FAISAL-BIEM DALAM PEMILIKADA GUBERNUR PROVINSI DKI JAKARTA 2012 - Sri Niken Handayani; Susilo Utomo; Purwoko . (Journal of Politic and Government Studies, 2013)
ABSTRACTDistatisfaction and dissapoinment people of political party, became anopportunity for independent candidate. Independent candidate is a someone who runfor the regional head such as governor, mayor city or regent without supported bypolitical party and have to collect personal identity as much as four percent of thepopulation. At the Jakarta’s governor election in 2012, two of six candidate was anIndependent candidate namely Fasial-Basri and Hendarji-Riza. Faisal-Biem havegained 5% vote had beaten Hendaji-Riza dan Alex Noerdin-Nono who supported byeleven political party.Starting from that picture, this research aims to understanding the politicalstragies of independent candidate Faisal and Biem. The method for this study isqualitative method.Data was collected by in-depth interview with several informantwho represented and several document was obtained in the field. The analytical databased on interview results.Results of this study have shown that the political strategies of independentcandidate used several new inovations in campaignings such as Saweran (collectmoney from people), using social media, created JELITA or Jejaring peduli Jakarta(Caring Jakarta Network) who in charged collecting personal identities of Jakarta’speople. There’s several reason to explain why the independent candidate lose inJakarta’s governor election such as Lack of popularity and lack of clearly mass baseas well as political party.Keyword : Independent Candidate, Local Election, Political Strategies